Enhanced multicast cluster-based routing protocol for delay tolerant mobile networks. (2015) - Anandakumar, H.; Nisha, K.
The delay-tolerant networks (DTNs) are a network designed to operate effectively over extreme distance. In DTNs, due to the unique characteristic of frequent partitioning, multicasting becomes a considerably different and challenging problem. In this paper we study multicasting in DTNs and propose a multicasting protocol, cluster-based multicast routing protocol (CBMRP), to support clustering in DTNs. Here multicast data transmission is simulated to transmit data to multiple destinations. Initially the distributed clusters are formed based on their EWMA values and depending on the services offered by mobile nodes inside the cluster, they are split into various groups. The data transmitted from source node is received by all the nodes of the group, in which the destination resides. The results show that our proposed protocol increase the network performance in terms of delivery rate as an epidemic routing scheme, and at a substantially lower overhead in multicast data transmission.